Multi-Physics Constraints at Different Densities to Probe Nuclear Symmetry Energy in Hyperonic Neutron Stars - Ghosh, Suprovo; Pradhan, Bikram Keshari; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Frontiers in Astronomy and Space Sciences, 2022)
The appearance of strangeness in the form of hyperons within the inner core of neutron stars is expected to affect its detectable properties such as its global structure or gravitational wave emission. In this work, we explore the parameter space of hyperonic stars within the framework of the Relativistic Mean Field model allowed by present uncertainties in state-of-the-art nuclear and hypernuclear experimental data. We impose multi-physics constraints at different density regimes to restrict the parameter space: Chiral effective field theory, heavy-ion collision data as well as multi-messenger astrophysical observations of neutron stars. We investigate possible correlations between empirical nuclear and hypernuclear parameters, particularly the symmetry energy and its slope, with observable properties of neutron stars. We do not find a correlation for the hyperon parameters and the astrophysical data. However, the inclusion of hyperons generates a tension between the astrophysical and heavy ion data constraining considerable the available parameter space.